Diversification of Peptidomimetics and Oligopeptides through Microwave‐Assisted Rhodium(III)‐Catalyzed Intramolecular Annulation. Issue 19 (13th August 2019) - Song, Liangliang; Tian, Guilong; Blanpain, Anna; Van Meervelt, Luc; Van der Eycken, Erik V.
Abstract: A chemoselective rhodium(III)‐catalyzed cascade annulation for the construction of the indolizinone and quinolizinone scaffolds is developed. Diversification of peptidomimetics and oligopeptides is achieved in a rapid and step‐economical manner through the combination of Ugi reaction and microwave‐assisted rhodium(III)‐catalyzed intramolecular annulation via C( sp 2 )‐H activation without installing a directing group. Abstract :